Case Report: Oral and fecal microbiota in a super-donor: the healthy microbiota paradigm for fecal transplantation - Ortiz-Olvera, Nayeli; Fernández-Figueroa, Edith A.; Argueta-Donohué, Jesús; Miranda-Ortíz, Haydee; Ruiz-García, Erika (Frontiers in Microbiomes, 2023)
Despite the numerous fecal microbiota transplantation trials that have been carried out, knowledge about the actual composition of a “healthy microbiota” remains scarce. The aim of this research was to describe the differences in the composition of oral and fecal microbiotas in a super-donor. The microbiota analysis was done using next-generation sequencing of the V3 and V4 regions of the bacterial 16S rRNA gene. The biodiversity found in the mouth was very rich, with 56 species identified, and there was a predominance of the genera Veillonella, Haemophilus, and Streptococcus. It is worth mentioning the presence (2.33%) of Fusobacterium nucleatum in the mouth. In feces, the genera Bacteroides and Faecalibacterium predominated, with the species F. prausnitzii being the most abundant. This analysis shows that the diversity of the microbiota of a super-donor plays a fundamental role in the effectiveness of its product in fecal matter transplantation. This suggests that transplanted gut microorganisms have the ability to maintain or recover health in a dynamic process between the microbiota and the host. Our findings encourage further research which will result in the development of bacterial therapies in infectious and inflammatory diseases.